Analisis Undang-Undang Zakat Nomor 23 Tahun 2011 terhadap Pendayagunaan Zakat Beasiswa Pendidikan - Rudy Gunawan; Shindu Irwansyah, Muhammad Yunus; Muhammad Yunus (Bandung Conference Series: Islamic Family Law, 2024)
Abstract. Zakat as a religious principle contains the goal of improving justice and community welfare. Education has great significance in shaping human values, skills, and personality. Zakat institutions that focus on education are regulated by Law Number 23 Year 2011. Zakat for education scholarship brings a positive impact on the access and continuity of education of underprivileged people, in accordance with Chapter III Article 27 of the Law. Zakat Law No. 23 Year 2011 regulates the provision of zakat for education, criteria for beneficiaries, transparency, accountability, and reporting and evaluation obligations. The distribution of zakat for education scholarship involves the stages of beneficiary identification, data verification, determination of the amount of assistance, and monitoring and evaluation. This process varies among zakat institutions. Zakat for educational scholarships can include tuition support, purchase of books and stationery, transportation, and general welfare. The implications of this finding provide insights for zakat institutions and contributions to the implementation of the Zakat Law in the context of education. Abstrak. Zakat sebagai prinsip keagamaan mengandung tujuan meningkatkan keadilan dan kesejahteraan masyarakat. Pendidikan memiliki signifikansi besar dalam membentuk nilai-nilai, keterampilan, dan kepribadian manusia. Lembaga zakat yang fokus pada pendidikan diatur oleh Undang-Undang Nomor 23 Tahun 2011. Zakat untuk beasiswa pendidikan membawa dampak positif pada akses dan kelangsungan pendidikan masyarakat kurang mampu, sesuai dengan Bab III Pasal 27 Undang-Undang tersebut. Undang-Undang Zakat No. 23 Tahun 2011 mengatur ketentuan pemberian zakat untuk pendidikan, kriteria penerima manfaat, transparansi, akuntabilitas, serta kewajiban pelaporan dan evaluasi. Penyaluran zakat untuk beasiswa pendidikan melibatkan tahapan identifikasi penerima manfaat, verifikasi data, penentuan besaran bantuan, hingga monitoring dan evaluasi. Proses ini bervariasi antar lembaga zakat. Zakat untuk beasiswa pendidikan dapat mencakup dukungan biaya pendidikan, pembelian buku dan alat tulis, transportasi, dan kesejahteraan umum. Implikasi temuan ini memberikan wawasan bagi lembaga zakat dan kontribusi pada penerapan Undang-Undang Zakat dalam konteks pendidikan.